2019
DOI: 10.3389/fonc.2019.00295
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Paradigm Between Leukocytosis, G-CSF Secretion, Neutrophil-to-Lymphocyte Ratio, Myeloid-Derived Suppressor Cells, and Prognosis in Non-small Cell Lung Cancer

Abstract: Leukocytosis is a common feature of malignancies. While controversial, there appears to be an association between the degree of tumor-related leukocytosis and prognosis. In this paper, we provide evidence supporting an untapped clinical paradigm linking G-CSF secretion to the induction of leukocytosis and expansion of myeloid-derived suppressor cells, providing an explanation for the association between leukocytosis, elevated neutrophil-to-lymphocyte ratios and prognosis in non-small cell lung cancer. Clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 42 publications
0
45
0
2
Order By: Relevance
“…Increasing evidence has indicated that some types of established cancers may actually accelerate the process of myelopoiesis, resulting in moderate, or even profound, leukocytosis, characterized by increased numbers of immature myeloid cells in the bone marrow, blood and spleen [25][26][27][28][29]. In this setting, accelerated myelopoiesis appears to result from the production of bone marrow-stimulating growth factors by tumor cells, most notably the cytokines granulocyte colony-stimulating factor (G-CSF) and granulocyte/macrophage colony-stimulating factor (GM-CSF) [30][31][32][33][34][35]. In this context, it is noteworthy that an increased circulating neutrophil/lymphocyte ratio (NLR, defined as the absolute circulating neutrophil count divided by the lymphocyte count) is widely regarded as being a negative prognostic indicator in many, but not all, types of cancer reviewed in [36].…”
Section: Recruitment and Exploitation Of Neutrophils By Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing evidence has indicated that some types of established cancers may actually accelerate the process of myelopoiesis, resulting in moderate, or even profound, leukocytosis, characterized by increased numbers of immature myeloid cells in the bone marrow, blood and spleen [25][26][27][28][29]. In this setting, accelerated myelopoiesis appears to result from the production of bone marrow-stimulating growth factors by tumor cells, most notably the cytokines granulocyte colony-stimulating factor (G-CSF) and granulocyte/macrophage colony-stimulating factor (GM-CSF) [30][31][32][33][34][35]. In this context, it is noteworthy that an increased circulating neutrophil/lymphocyte ratio (NLR, defined as the absolute circulating neutrophil count divided by the lymphocyte count) is widely regarded as being a negative prognostic indicator in many, but not all, types of cancer reviewed in [36].…”
Section: Recruitment and Exploitation Of Neutrophils By Tumorsmentioning
confidence: 99%
“…Targeting of the G-CSF/MDSC axis is an attractive option [35], which is attainable in the experimental setting via the administration of mAbs that neutralize G-CSF directly or block its receptor expressed on bone marrow precursor cells [129]. However, such a strategy is impractical in the clinical setting since it presents an unacceptably high risk of severe neutropenia and development of life-threatening microbial infection.…”
Section: Cytokine Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppressive cells, such as bone marrow-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs), and regulatory T (Treg) cells, act as suppressive TIME components to attenuate immune responses [2]. Among these cells, MDSCs have roles in the prognosis, development, and treatment of LC that have been paid increasing attention [3,4]. MDSCs are a group of highly heterogeneous cells derived from immature myeloid progenitors that are usually divided into two subpopulations: polymorphonuclear MDSCs (PMN-MDSCs) and monocytic MDSCs (M-MDSCs) [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Additional proposed markers of response include neutrophil‐to‐lymphocyte ratio (NLR), which has been reported to increase over time in non‐responders and decrease in responders, and inflammatory cytokines, which have also been correlated with response rates and toxicity 72–78 (Figure 3). Myeloid‐derived suppressor cell (MDSC) levels have been used to predict therapy response or resistance to ipilimumab treatment in metastatic melanoma patients, where increased frequency was associated with decreased efficacy, and vice versa 79,80 .…”
Section: Novel Ici Approaches To Precision Oncologymentioning
confidence: 99%